Text Modality as a Mode of Value-based Representation of Tuva in German Opinion Journalism - Komutstsi, Liudmila V.; Karpunina, Irina V. (The New Research of Tuva, 2021)
The aim of the article is to characterize the value representation of Tuva in opinion texts published in German language media by analyzing their modality. The features of different types of modality and their correlations in the text have attracted a close attention of Russian linguists since the 1990s. This issue is of particular importance in media linguistics because textual modality is the most important but not always explicit way of expressing a value standpoint and a journalist’s subjective assessment of events and phenomena. The study material consists of 30 articles on the Republic of Tuva published in 2012–2021 in digital versions of newspapers and magazines (“Frankfurter Allgemeine Zeitung”, “Süddeutsche Zeitung”, “Die Welt”, “Explorer”, “Die Tageszeitung”, “Der Spiegel”, “Focus” and “Die Zeit”). The research is novel because of the fact that the linguistic means of modality in German language texts, especially in opinion pieces, are poorly studied in Russia. As a method and tool of analysis the authors use the category of the modal grid of the text. With its help they trace the development of the axiology of publications on Tuva. The results of the analysis show that Tuva is presented in the latest media discourse of Germany not from critical perspectives, but as a region that has a unique history, nature and culture.